Beginning Gardening Unit I: Growing Vegetables in Containers - James M. Stephens; Susan D. Gray (EDIS)
This document is 4HGRM02 of the Florida 4-H Youth Development Program, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Produced August 1979, revised May 1996, Reviewed June 2002.